Household pre‐purchase practices and online grocery shopping. Issue 5 (9th May 2014) - De Kervenoael, Ronan; Hallsworth, Alan; Elms, Jonathan
ABSTRACT This paper explores household pre‐purchase practices and their mediation by information and communications technologies (ICTs), specifically online grocery shopping. Drawing on practice theory, the impacts of ICTs on household grocery shopping behavior are conceptualized, and the concept of "front‐loading" is introduced. Emerging themes generated from 31 semi‐structured interviews conducted via Skype with Turkish consumers focusing on their experiences of online grocery practices are presented. To this end, the contribution of this paper is twofold. First, an understanding of the domestication of online grocery shopping and its affect on the dynamics of household decision making, information sharing, and responsibilities of tasks before the actual act of online shopping is developed. Second, how such pre‐purchase practices undertaken by consumers act as a catalyst of change at the industry level is appraised. Copyright © 2014 John Wiley & Sons, Ltd.